Komunikasi Partisipatif Masyarakat Industri dalam Mendukung Branding Kota Madiun - Dewi, Mutia; Nulul, Noer Ayufika (FISIP Universitas Atma Jaya Yogyakarta, 2018)
Industrial society in madiun city contribute in supporting of Madiun city branding. This proved by the participate position in implementation and utilization of results. Madiun industrial society show the competitive value to global society that usually earn achievement from the exhibition that helds from many various events. Â This competitive value is suitable with creation of Madiun city branding as 'Kota Gadis' which combinate from three education aspects. The form of communication participation in supporting branding madiun city is heteroglasia,dialogis, poliponi, dan karnavalÂ